PERLINDUNGAN HUKUM TERHADAP PROFESI NOTARIS DALAM PEMBUATAN PARTIJ AKTA - Subiyanto Subiyanto (UNISSULA, 2016)
The legal acts clients who come to the notary. Formulated into an authentic deed in accordance with the authority of a notary, and then the notary made the deed at the request of the client. Therefore, the notary must ensure that the deed made it complies according to the legal rules that have been determined, so that the interests of concered are protected with such deed. A notarial deed is an authentic deed made according to the forms and procedures set in this constitution. Notary bound with the truth formil because of the liability according UUJN, if the parties dispute, so notary can not be punished.